E.T.A. Hoffmann e a cegueira esclarecida - Munk, Leonardo (Contingentia, 2008)
Considering the European mentality of the first half of the 19th century, this article discusses the important role of E. T. A. Hoffmann in the literature of that period. The text deals specially with Hoffmann’s critique of the superiority of reason over imagination. Cultivating the grotesque and the supernatural, Hoffmann criticizes the bourgeois attitudes towards an unquestioned belief in the reason as the unique savior of mankind.